Impact of Remuneration for Work on Social Changes in Lithuania - Gruževskis, Boguslovas; Sudnickas, Tadas; Urbanovič , Jolanta (Edukacja Ekonomistów i Menedżerów, 2018)
Satisfaction with compensation for work in modern society, especially in welfare states, plays a very important role. It not only ensures the efficient use of available production facilities and natural resources, but also determines the size of the state budget, the quality of life in the country, an attitude towards emigration and the general state of social situation. In a market economy, wages are the expression of capital and labour relations, both at the national and at the company level. The compensation systems are also influenced by some external factors such as tax system, technological level, labour supply and demand balance and legal regulation. The article seeks to reveal how the satisfaction with pay for work affects the social changes in the country. The article present the results of the research carried out in Lithuania in 2017.